The Effect of Talent Management and Work Motivation on Employee Performance at PT Cipta Niaga Semesta - Philip Obelafu; Asep Jamaludin; Nandang Nandang (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study aims to examine the effect of talent management and work motivation on employee performance at PT Cipta Niaga Semesta. The method used is descriptive quantitative with an explanatory survey design to explain the relationship between research variables. Data was collected through a survey using a questionnaire as primary data, as well as using secondary data from related scientific books and journals. The research population is employees of PT Cipta Niaga Semesta, with a sample of 47 respondents. The analysis uses multiple linear regression and the coefficient of determination to identify the influence of talent management and work motivation variables on employee performance. The t test is used to test the individual effect of the independent variables on the dependent variable, while the F test is used to test the simultaneous effect of the independent variables on the dependent variable. The results of the analysis show a significant t value for the talent management variable (7.206) and motivation variable (3.439). This shows that talent management and motivation have a significant effect on employee performance. Therefore, companies need to manage these two factors optimally to achieve high employee performance. This research also supports the findings of previous studies which show a positive relationship between talent management, motivation, and employee performance.